Inventários de arquitetura moderna no Brasil: desnaturalizando uma prática estabelecida - Guedes, Kaline Abrantes (2018)
Reflecting on the theoretical foundations and instruments that guide the practice and production of inventories of modern architecture in Brazil is the main objective of this doctoral work. whose focus is to analyze the bases on which architectural inventories were traditionally built and how they are currently built. Therefore, we have identified, located, collected, and analyzed various inventories of modern architecture produced in Brazil. Coming closer to De Certeau's (1982 [1974]) historiographical lessons, it is important to understand: where do the methods from which these inventories are developed come from; which documents and questions have been privileged for elaborating these records; which of them have been neglected (unspoken). It is interesting to know what would be the specifics of a modern inventory, of an experimental architectural production with the purpose of breaking paradigms, and using technological advancements to their limit, what is the importance of architectural design and the modern concepts of “flexibility”, “transparency”, “exterior/interior relationship”, inter alia. It is also interesting to analyze the importance of the Docomomo model or the models applied to previous architectural productions, and how recent discussions and theoretical studies on related themes are being addressed. In Brazil, it is only in the 1980s that the inventory officially becomes a preservation instrument, through art. 216, §1 of the Brazilian Constitution of 1988, which states that “Public Authorities, in collaboration with the community, shall promote and protect the Brazilian cultural heritage through inventories, records, monitoring, landmarking and expropriation, and other forms of protection and preservation” (BRAZIL, 2004). For Prudon (2008, p. 23), the preservation of modern architecture has its peculiarities and one of the essential distinctions between this “and that of traditional productions is the need for extremely accelerated substitution – and all the philosophical questions that it engenders.” What then would be the role of modern inventory in this process, and how this instrument of preservation and documentation could address these peculiarities to act in the preservation of the examples of this architectural production? It is necessary to think and rethink the role of inventories in the writing of history, its objectives and its methods, to advance the production of knowledge, constantly evaluating it, facing new problems, including new questions, and feeding suspicions.